Proper selection of personnel for the Security Service of Ukraine as a prerequisite for the career growth of its employees - M. S. Yuzyshen (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The current state of national legislation regarding the establishment of a list of requirements for candidates for service in bodies and units of the Security Service of Ukraine has been considered. The achievements of scholars on the essence of personnel selection, career, and labour legal personality of employees have been studied. The peculiarities of the legal personality of employees of the Security Service of Ukraine have been determined.